Christmas in Icicle Falls - Roberts, Sheila, 1951- (Roberts, Sheila. 1951- Life in Icicle Falls., 2017)
When Muriel Sterling released her new book, A Guide to Happy Holidays, she felt like the queen of Christmas. She<U+2019>s thrilled when the new tree she ordered online arrives and is eager to show it off<U+2014>until she gets it out of the box and realizes it<U+2019>s a mangy dud. But rather than give up on the ugly tree, Muriel decides to make a project out of it. As she pretties up her tree, she realizes there<U+2019>s a lesson to be learned: everything and everyone has potential. Maybe even her old friend Arnie, who<U+2019>s loved her for years. Except, she<U+2019>s not the only one seeing Arnie<U+2019>s potential<U+2026> Meanwhile, Muriel<U+2019>s ugly-tree project has also inspired her friends. Sienna Moreno is trying to bring out the best in the grouchy man next door, who hates noise, hates kids and hates his new neighbors. And while Olivia Claussen would love to send her obnoxious new daughter-in-law packing, she<U+2019>s adjusting her attitude and trying to discover what her son sees in the girl. If these women can learn to see the beauty in the “ugly trees” in their lives, perhaps this might turn out to be the happiest holiday yet.